The influence of diffusion in the fracture resistance method for wellbore strengthening: A rock mechanics approach - Sarris, Ernestos; Aladeyelu, Abdullahi; Gravanis, Elias (My University, 2018)
© 2018 Author(s). A coupled finite element model was constructed to investigate the influence of diffusion in the fracture resistance method for wellbore strengthening. We simulate the unwanted fluid-driven fracture that is created from a narrow drilling mud window with the cohesive zone approach in a poroelastic formation. The fluid flow within the fracture is modelled by the lubrication theory assuming incompressible Newtonian viscous fluid while the fluid movement in the formation follows the Darcy law. The deformation of the porous continuum is considered to obey the Biot effective stress principal. Plugging is simulated by shutting-in the flow rate at the well and constraining the fracture aperture at a 1m distance from the well so as to allow the fluid to bleed in the formation. From the poroelastic analysis, we obtain the fracture dimensions, fluid pressures, in-situ stress field change and the principal stresses during injection and plugging the fracture. From the principal stresses, we apply a normalized Griffith criterion suitable for predicting fracture onset. It was found that during plugging, the fracture tip effectively resists propagation, however, a new fracture is predicted to onset at the plug location owing to the diffusion of drilling fluids from the fracture towards the formation causing severe stress concentration compared to elastic models which fail to predict such physical mechanisms.
Keywords: Drilling fluids; Oil field equipment; Wellbore strengthening